2021
DOI: 10.3390/joitmc7030167
|View full text |Cite
|
Sign up to set email alerts
|

Application of Blockchain for Supply Chain Financing: Explaining the Drivers Using SEM

Abstract: Owing to the lack of research in emerging Asian nations, this research aimed to unearth the determinants of blockchain acceptance for supply chain financing by a Bangladeshi financing company called IPDC. Centred on a technology acceptance framework called UTAUT (unified theory of acceptance and use of technology) and open innovation research, an expanded model with a mediating variable is developed for this study. This research work employs the deductive inference method in conjunction with the positivism par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 158 publications
(281 reference statements)
0
20
0
Order By: Relevance
“…In studies on intention to use technology, trust was also found to have a positive effect on effort expectancy and intention to use (Lee and Song, 2013;Zhou, 2014). Besides, trust is the construct that is used mainly in studies investigating blockchain intentions because of its important role in improving performance (Wong et al, 2020;Kabir and Islam, 2021). Based on these discussions, we propose the following hypotheses:…”
Section: Trust According Tomentioning
confidence: 92%
See 2 more Smart Citations
“…In studies on intention to use technology, trust was also found to have a positive effect on effort expectancy and intention to use (Lee and Song, 2013;Zhou, 2014). Besides, trust is the construct that is used mainly in studies investigating blockchain intentions because of its important role in improving performance (Wong et al, 2020;Kabir and Islam, 2021). Based on these discussions, we propose the following hypotheses:…”
Section: Trust According Tomentioning
confidence: 92%
“…However, as far as the adoption of blockchain technology is concerned, some studies suggested that constructs in UTAUT are still lacking. The authors use UTAUT's original constructs as mediating role, or they adapt these constructs to the context of the study (Wamba and Queiroz, 2019; Wong et al , 2020; Kabir and Islam, 2021; Alazab et al , 2021). With auditing, a field closely related to accounting, Ferri et al (2020) extended the UTAUT model to assess the intentions of auditors to use blockchain.…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers are now competent in using technology owing to quick digitalization during the COVID-19 pandemic. Therefore, online survey is a better technique to undertake a helpful survey recognizing time and physical travel restrictions (Kabir et al , 2021). Browne (1995) suggests that a common rule of thumb for approximating a measure is to use 30 or more sample size.…”
Section: Methodsmentioning
confidence: 99%
“…In the following, we describe some of the most common BC applications. For the sake of completeness, other interesting ones are reported in Table 3 where Application field [115] 2021 Application of BC for the sustainability of Prefabricated Housing Construction [116] 2021 Barriers for adopting BC technology in sustainable supply chains [117] 2021 Constructing a smart city IoT framework with BC and SDN that is energy aware and distributed securely [118] 2021 Blockchain application for supply chain in the area of construction industry [119] 2021 Blokchain technology for the safety of the management of food data [120] 2021 Application of Blockchain for financial sector [121] 2021 BC-based architecture for intelligent vaccine distribution approaches in COVID-19 pandemic situation [122] 2021 Integration of Blockchain for Supply chain management [123] 2021 Blockchain-based privacy for smart healthcare management [124] 2020 Impact of BC on applications covering different industrial sectors [125] 2020 Effects of BC technology on the logistics industry and other business models [126] 2020 Framework for the analysis of BC integrating institutional, market, and technical factors [127] 2020 BC-based decentralized app for smart building system management [128] 2020 Blockchain-based security for cloud storage management in IoT networks [129] 2019 Applications in the architecture, engineering, and construction industries [130] 2019 BC-enabled SCs in different application scenarios (e.g., finance, energy, etc.) [131] 2019 Review of the BC systems exploited in the oil and gas industry [132] 2019 Main trends of BC usage in supply chains management and logistics [133] 2019 SDN-IoT model with NFV implementation for smart cities based on a distributed protected BC architecture [134] 2019 Applications for smart communities (e.g., smart grid, transportation, healthcare) [135] 2018 BC-connected gateways to maintain user privacy in IoT networks [136] 2018 LedgerGuard: a tool for ledger integrity, detecting and recovering corrupted blocks [137] 2018 Patient monitoring system using SC and private BC based on the Ethereum protocol Table 3 (continued)…”
Section: Blockchain Applicationsmentioning
confidence: 99%